Analysis of Factors Correlated with the Incidence of Obesity In Women of Productive Age - Revi Rosavika Kinansi; Zahroh Shaluhiyah; Martha Irene Kartasurya; Dwi Sutiningsih; Matheus Sakundarno Adi; Wening Widjajanti (GLOBAL HEALTH SCIENCE GROUP, 2023)
Obesity is excessive accumulation of fat due to an imbalance between energy intake and energy expenditure. This study aims as a community diagnosis to determine the respondent's body mass index and to determine the risk factors that have a reciprocal effect on the nutritional status of the community. This study uses a cross sectional method with a descriptive approach and using a backward logistic regression method: Wald. Data collection is carried out to the population was 55 women who met the inclusion criteria aged 21-65 years and were willing to become respondents. The results of this study, obtained information that the age of the respondent has a significant influence on the obesity status of the community with a significant value of 0.043 with an opportunity of 1.072 times. Likewise, the respondent's work has a significant value of 0.015, this provides information that the more the respondent do the physical activity, can protect the body from obesity status by 1.940 times or almost 2 times for the better. Obesity has a chance of 0.065 times affecting the incidence of hypertension with p-value 0,011. Not only that, a person's stomach circumference is closely related to the incidence of obesity with a p-value of 0.019 and an odds ratio value of 5.019. Eating packaged food such as instant noodles which is often done by respondents has a significant effect on obesity status of 0.059. Instant food will have a negative effect of 3 times of obesity.